Ultrasonographic evaluation of first trimester vaginal bleeding - Vidya A. Thobbi; Gururaj Deshpande; Uma A Salma Afreen; Ruma Nooreen (Al Ameen Medical College, 2016)
Objective: Precisely identifying the incidence and causes of vaginal bleeding occurring in first trimester by clinical and transvaginal ultrasonography and to assess the outcome and to institute appropriate obstetric management. Materials and Method: A Cross-sectional study done in 100 patients attending Al-Ameen hospital with historyof bleeding per vagina in first trimester during the 2013-2014 (study period). Study subjects were examined and USG was performed. Result: In our study the age group ranged from 16-35 yrs and majority of study subjects belonged to 21-25 years, constituting percentage of 46and majority of patients were primigravida constituting 60%. In our study, mean gestational age at which cases presented with bleeding in first trimester was 9 weeks. Majority of the cases that is 35 of them with bleeding per vagina were between gestational ages 6-8 weeks. Conclusion: In present study ultrasound has helped in diagnosing and confirming most of the cases of first trimester vaginal bleeding.